Analisis Faktor-Faktor Yang Mempengaruhi Peluang Konsumen Terhadap Keputusan Pembelian Batik Di Kawasan Batik Trusmi Cirebon. - Faulika Dwi Astuti (Jurnal Riset Mahasiswa, 2020)
Sales of batik in the Trusmi Cirebon Batik Area in 2017 experienced a very drastic decline, reaching 50.8%. This decline was caused by internal factors, namely the competitiveness of batik sales between stores and showrooms and another factor was the increase in Chinese printed batik entering Indonesia. This study used a sample of 100 respondents. The method used in this research is descriptive quantitative method. The regression model used is the probit nonlinear regression model. Based on the analysis of the research that has been done, it is found that the average age of consumers is 16-31 years old with 70% of consumers being women. As many as 64% of consumers have a D3/S1 education with 65% of consumers having a type of work in the private sector. Another conclusion obtained is that age and education variables have a significant effect on batik purchasing decisions.